Strategi Pemasaran Sapi Potong di CV Septia Anugerah Jakarta - Tonni Kusuma; Sapta Raharja; Amiruddin Saleh (Institut Pertanian Bogor, 2013)
CV Septia Anugerah is one of the largest beef cattle in Indonesia that can meet the needs of beef cattle. In West Java, beef marketing largely dominated by livestock or livestock. The company helps farmers with livestock marketing and make it easier for farmers to get cash when needed. Marketing beef cattle through marketing channels can make the commodity reaches the consumer. But inefficient channel marketing can be relatively long or causing harm to farmers and consumers, the consumers bear the high cost of marketing, so pay a higher price, farmers are earning less, because the selling price is lower as well. In this study used the total score to produce a matrix of IFE and EFE are respectively 2,696 and 2,793 indicating that the CV Septia Anugerah is in a stable position to respond to the external environment and in a position to respond to factor flats internal. The total value score of IFE and EFE second is to identify the position of CV Septia Anugerah. Value matrix IE indicates the position of the middle cell (V), which is the growth/stable. The results of the analysis of SWOT is the following strategies, namely, the need to implement a combination of the four aspects of marketing (4Ps): product, price, place and promotion). Managerial implications of the aspects under study can be grouped into four: (1) marketing, (2) financing, (3) production, and (4) human resources. Based on matrix computations Quantitative Strategic Planning (QSP), the most interesting to be applied is to expand the marketing network to penetrate the market with the highest value of the appeal.